Effect of Prayer on Intensity of Migraine Headache - Haleh Tajadini MD, PhD; Nasser Zangiabadi MD; Kouros Divsalar; Hossein Safizadeh MD; Zahra Esmaili; Hossein Rafiei (SAGE Publishing, 2017)
Background and Aim. Migraine is a common form of headache that affects patients quality of life negatively. In addition to pharmacologic treatment, there are a variety of nonpharmacologic treatments for migraine headache. In present study, we examined the effect of prayer on intensity of migraine pain. Methods. In a prospective, randomized, controlled trial from October 2013 to June 2014, this study has been conducted in Kerman, Iran. We randomly assigned 92 patients in 2 groups to receive either 40 mg of propranolol twice a day for 2 month (group "A") or 40 mg of propranolol twice a day for 2 months with prayer (group "B"). At the beginning of study and 3 months after intervention, patients' pain was measured using the visual analogue scale. Results. At the beginning of study and before intervention, the mean score of pain in patients in groups A and B were 5.7 ± 1.6 and 6.5 ± 1.9, respectively. According to results of independent t test, mean score of pain intensity at the beginning of study were similar between patients in 2 groups ( P > .05). Three month after intervention, mean score of pain intensity decreased in patients in both groups. At this time, the mean scores of pain intensity were 5.4 ± 1.1 and 4.2 ± 2.3 in patients in groups A and B, respectively. This difference between groups was statistically significant ( P < .001). Conclusions. The present study revealed that prayer can be used as a nonpharmacologic pain coping strategy in addition to pharmacologic intervention for this group of patients.